Collecting Objects / Excluding People : Chinese Subjects and American Visual Culture, 1830-1900 - Metrick-Chen, Lenore (Book collections on Project MUSE., 2012)
"Combining aesthetic and political history, explores the influence of Chinese people and objects on American visual culture. In Collecting Objects / Excluding People, Lenore Metrick-Chen demonstrations an unknown impact of Chinese immigration upon nineteenth-century American art and visual culture. The American ideas of "Chineseness" ranged from a negative portrayal to an admiring one and these varied images had an effect on museum art collections and advertising images. They brought new ideas into American art theory, anticipating twentieth-century Modernism. Metrick-Chen demonstrates that efforts to construct a cultural democracy led to the creation of unforeseen new categories for visual objects and unanticipated social changes. Collecting Objects / Excluding People reveals the power of images upon culture, the influence of media representation upon the lives of Chinese immigrants, and the impact of political ideology upon the definition of art itself."--Project Muse